FAKTOR PENDUKUNG PERILAKU BERALIH LAYANAN PERBANKAN KE LAYANAN PEMBIAYAAN BERBASIS FINANSIAL TEKNOLOGI - Pradnyani, Ni Luh Putu Sri Purnama; Artaninggrum, Rai Gina (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2021)
This study aims to determine the factors driving service switching behavior in the form of pricing, service quality, competition, reputation, response to failure, service products, and forced switching that can influence borrowers to switch to using financing services from banks to financial technology-based financing services (crowdlending). The research sample was 94 people who met the research criteria. The analysis technique used to answer the research hypothesis is multiple linear regression analysis. The results show that banking price determination affects a person's switching behavior from banking-based financing services to crowdlending services. Service quality affects the behavior of switching to financial technology-based financing services (crowdlending). Competition affects the behavior of switching to financial technology-based financing services (crowdlending). Reputation affects the behavior of switching to financial technology-based financing services (crowdlending. Response to failure affects the behavior of switching to financial technology-based financing services (crowdlending). Service products do not affect the behavior of switching to financial technology-based financing services (crowdlending). Forced transition has no effect on the behavior of switching to financial technology-based financing services (crowdlending) Simultaneously determining prices, service quality, competition, reputation, response to failure, service products, and switching are forced to use financing services from banks to crowdlending financing services.